The Sound Masking Assessment of Recycled Partition - Phylicia Deosephine Soegiono; Feny Elsiana; Lilianny Sigit Arifin (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2024)
The increasing rate of urbanization leads to more unmanaged waste, currently at 33.08% of 18 million tons per year. This research uses recycled cans as architectural elements to address the acoustic comfort issues in coworking spaces. Some of these studies have also recommended the addition of sound masking elements such as natural sounds, music, and others to enhance workers' productivity. Furthermore, earlier research has experimented with processing waste plastic materials into acoustic elements based on sound absorption theory. The aim of this research is to conduct experiments by using recycled waste cans as an architectural element that can function as sound masking, providing an acoustically comfortable sound range that supports users' well-being. Results show that recycled partitions placed between workers produced a sound intensity level of 57.6 dBA, which is still 7.6 dBA above the comfort threshold.